ISLAM DAN PORNOGRAFI-PORNOAKSI (Menakar Solusi Perspektif Hukum Islam) - Mth, Asmuni (Al-Mawarid Jurnal Hukum Islam, 2006)
Pornography and pornoaction happen because of modernization and globalization influence on sosiety lives. Without consciousness from society to solve the above problems which considering Islamic community public interest, pornography and pornoaction always emerge. Islam as doctrine early presents to solve the problems, so there are many Quranic verses and prophet traditions regulate the dress, communication between man and woman, including the publications that appear moral decadence. Kata kunci: pornografi, pornoaksi, Islam, fiqh.